PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, MOTIVASI TERHADAP KINERJA PEGAWAI NEGERI SIPIL DINAS SOSIAL KABUPATEN BENGKALIS - Juanda, Juanda; Zulfadil, Zulfadil; Samsir, Samsir (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to determine how the influence of Leadership, WorkEnvironment and Motivation Against the Performance of Civil Servants SocialAffairs Bengkalis Regency. The Sampling in this research using technique of nonprobability sampling (Purposive Sampling), and sample which included in thisresearch amounts 70 civil servants in the room Scope of Social Service ofBengkalis Regency. In this study the independent variables are Leadership (X1),Work Environment (X2), Motivation (X3) and Performance (Y) by Using Analysisof Two-Stage Regression Data. The research Found that Leadership X1, WorkEnvironment (X2) and Motivation (X3) have significant effect on PerformanceVariable (Y) on Civil Servant of Social Sub-Bureau of Bengkalis Regency. Thisresearch uses two-stage regression, which for the first stage tested the leadershipvariable (X1) and Work Environment (X2) on Motivation (X3), the result ofdominant Work Environment is significant to Motivation Variables. While insecond regression test, the result of Leadership variable (X1), Work Environment(X2) and Motivation (X3) have an effect on Performance variable (Y).